1996
DOI: 10.1016/0167-4889(96)00004-3
|View full text |Cite
|
Sign up to set email alerts
|

Complete inhibition of poly(ADP-ribose) polymerase activity prevents the recovery of C3H1OT1/2 cells from oxidative stress

Abstract: Activation of the poly(ADP-ribose) polymerase after oxidative damage is implicated in different responses of the cells, for example, cell recovery after sublethal damage or cell death after lethal damage. However, the extent and mechanism of involvement of the enzyme in these two processes appear to be different. Inhibitors of this polymerase, such as benzamides, which do not completely inhibit PARP have been shown to protect the cells from killing by massive oxidant damage, could neither reduce the cellular r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Cells treated with inhibitors of PARP have been reported to become resistant to various genotoxic agents, such as UVB-and ␥-irradiation, tumor necrosis factor (TNF), alkylating agents, and free radicals (Malorni et al 1995;McGowan et al 1996). In contrast, other studies showed that inhibition or a dominantnegative mutation of PARP sensitizes cells to cell death induced by oxidative stress, alkylating agents, ␥-irradiation, or heat shock (Nosseri et al 1994;Kü pper et al 1995;Schreiber et al 1995;Shah et al 1996). Although results obtained from these studies are contradictory and the mechanisms involved in such processes are complex, the function of PARP is well documented in free radicalinduced cell toxicity in neurons and pancreatic islet cells (Zhang et al 1994;Heller et al 1995).…”
Section: Nadmentioning
confidence: 92%
“…Cells treated with inhibitors of PARP have been reported to become resistant to various genotoxic agents, such as UVB-and ␥-irradiation, tumor necrosis factor (TNF), alkylating agents, and free radicals (Malorni et al 1995;McGowan et al 1996). In contrast, other studies showed that inhibition or a dominantnegative mutation of PARP sensitizes cells to cell death induced by oxidative stress, alkylating agents, ␥-irradiation, or heat shock (Nosseri et al 1994;Kü pper et al 1995;Schreiber et al 1995;Shah et al 1996). Although results obtained from these studies are contradictory and the mechanisms involved in such processes are complex, the function of PARP is well documented in free radicalinduced cell toxicity in neurons and pancreatic islet cells (Zhang et al 1994;Heller et al 1995).…”
Section: Nadmentioning
confidence: 92%
“…However, NAD levels continued to drop after the polymer peak, even though more than 50% of PARP was cleaved. A concentration of 1 mM of the PARP inhibitor DHQ, known to completely inhibit PARP in vivo (26), only partially prevented the loss of NAD (Fig. 2B).…”
Section: Parp Cleavage By Caspases At the Time Of Its Activation-mentioning
confidence: 99%
“…The automodification reaction was stopped by the addition of 100 M DHQ (26). Upon addition of 0.1% CHAPS and the indicated amount of caspase-3 or -7, the substrate was digested for specific times at 37°C.…”
Section: Materials-[mentioning
confidence: 99%
“…NAD ϩ was added to reactions as indicated, and arrows indicate the position of phosphorylated RPA p34 and phosphorylated p53 proteins. dihydroxyisoquinoline (DHQ) (37). In the presence of 1 mM DHQ the automodification activity of PARP in the presense of 200 M NAD ϩ is nearly completely inhibited (Fig.…”
Section: A Lane D)mentioning
confidence: 99%